A review of thin layer drying of foods: theory, modeling, and experimental results. - Erbay Z; Icier F; Erbay, Zafer; Icier, Filiz (Critical Reviews in Food Science & Nutrition, 2010)
Drying is a complicated process with simultaneous heat and mass transfer, and food drying is especially very complex because of the differential structure of products. In practice, a food dryer is considerably more complex than a device that merely removes moisture, and effective models are necessary for process design, optimization, energy integration, and control. Although modeling studies in food drying are important, there is no theoretical model which neither is practical nor can it unify the calculations. Therefore the experimental studies prevent their importance in drying and thin layer drying equations are important tools in mathematical modeling of food drying. They are practical and give sufficiently good results. In this study first, the theory of drying was given briefly. Next, general modeling approaches for food drying were explained. Then, commonly used or newly developed thin layer drying equations were shown, and determination of the appropriate model was explained. Afterwards, effective moisture diffusivity and activation energy calculations were expressed. Finally, experimental studies conducted in the last 10 years were reviewed, tabulated, and discussed. It is expected that this comprehensive study will be beneficial to those involved or interested in modeling, design, optimization, and analysis of food drying.